Espinélios do sistema Mg2TiO4-Mg2SnO4 obtidos pelo método Pechini-modificado: propriedades fotocatalíticas e antiadesão microbiana - Lima, Laís Chantelle de (2016)
Magnesium stannate (Mg2SnO4) and titanate (Mg2TiO4) are inverse spinel-type oxides, applied as humidity sensors, hot resistor, dieletric, temperature compensation capacitor, electronic ceramic and refractory material. In the present work, these two materials were combined in order to obtain a solid solution, Mg2(Ti1-xSnx)O4, (x = 0; 0,25; 0,50; 0,75; 1,0) by the modified-Pechini method, in order to investigate the influence of Sn4+ substitution for Ti4+ in the spinel lattice for application as photocatalyst for discoloration of Gold yellow remazol and to avoid micro-organism adhesion into surfaces. The synthesis of the spinels was optimized. Catalysts were characterized by X-ray diffraction, UV-visibe spectroscopy, Raman spectroscopy, infrared spectroscopy, surface area measurement using BET method. Mg2TiO4 is a metastable compound, which decomposes into ilmenite (MgTiO3) above 800 °C. On the other hand, reaches long-range order at lower temperatures, while single phase Mg2SnO4 is only obtained from 900 °C. For these reasons, different temperatures are necessary to obtain the single phase materials. Infrared and Raman spectra confirmed the presence of [MgO6]-10, [TiO6]-8, [SnO6]-8 octahedra and (MgO4)-6 tetrahedra. The photocatalytic tests were carried out in a reactor comprising of UVC lamp (λ = 254 nm). Mg2SnO4 presented the best photocatalytic result, with 79% of discoloration at pH 6 and 87% at pH 3, while Mg2TiO4 showed 7% of conversion at pH 6, without increasing efficiency at pH 3. The obtained spinels were effective in inhibiting bacterial and fungal growth as indicated by fluorescence analysis for Gram positive bacteria (S. aureus and S. mutans), Gram negative bacteria (P. aeruginosa and E. coli) and fungus (Candida albicans) showing the potential for microbial anti-adhesion material. Tests with higher titanium content showed the best results except for E. coli.